PENERAPAN E-LEARNING UNTUK MENDUKUNG PENINGKATAN KOMPETENSI PAMONG BELAJAR - Muktiono Waspodo (JIV-Jurnal Ilmiah Visi, 2010)
Learning civil competency improvement is needed in order to support implementation of the basic task. Educators on Learning as a civil nonformaJ channels also need to learn. This requires a systematic and continuous efforts to innovate learning for Civil Education. one of them is by using e-learning programs for the improvement of civil competence study. Need to be prepared carefully to develop e-learning, that can be utilized by the Civil Learning.